Prosody in contact: polar questions in Cypriot varieties of Greek and Turkish - Payne, E; Armostis, S; Lombardo, E; Simon, R; Baltazani, M (Guarant International, 2023)
Cypriot varieties of Greek (CYG) and Turkish (CYT) have been in close contact for many centuries, leading to mutual influence (e.g. lexical borrowings), despite belonging to different language families, and being typologically distinct. Little empirical research has been conducted on prosodic influence between contact languages. Some analyses of CYT polar questions report similarities with CYG, but do not give quantitative results. Using quantitative modelling of intonational contours, we compare CYG polar questions with those in CYT (geographically close), and with those in Athenian Greek (ATG) (phylogenetically close). We confirm previous research showing CYG questions are phonologically very similar to ATG, albeit with phonetic differences. We also find these patterns in CYG speakers’ L2 English. We then compare CYT questions with those in Istanbul Turkish (IST) and find, in contrast, both Greek-like variants (presumably due to contact with CYG), and more Turkish-like variants, with distribution likely conditioned by sociolinguistic factors.